RELATIONAL CAPITAL INFLUENCE ON BUSINESS PERFORMANCE: THE MODERATING ROLE OF ISLAMIC WORK ETHICS - Sakinah Mat Zin; Khamisah Abd Manaf; Engku Huda Mursyidah Engku Hassan Ashari; Baba Uba Ibrahim (Journal of Islamic, Social, Economics and Development, 2024)
This paper draws on resource-based theory (RBV) to examine the impact of relational capital and Islamic work ethics on business performance through the moderating role of Islamic work ethics in small and medium-sized enterprises (SMEs). SMEs make up 38.4% of Malaysia's gross domestic product. Despite the significance of this sector, it has received insufficient focus in terms of relational capital and its integration with Islamic work ethics for assessing organizational performance. This study employs a cross-sectional design, and data are gathered through questionnaires that are completed by SME entrepreneurs. The convenient sampling method is utilized, selecting participants from a sampling frame consisting of entrepreneurs in Kelantan, Malaysia. The sampling frame used in this study is SME entrepreneurs registered with the Malay Chamber of Commerce Malaysia Kelantan (DPMMK), an organization signifying and attending the Malay businesspeople in Kelantan. A total of 445 entrepreneurs engaged in SMEs across various districts in Kelantan are invited to complete the questionnaires. PLS-SEM is used in performing data analyses for this study. The results reveal that Islamic work ethics have a significant and positive influence on business performance, but relational capital has no relationship with business performance. Furthermore, Islamic work ethics significantly moderates the relationship between relational capital and business performance. The development programs and policies should focus on improving the relational capital and Islamic work ethics of SME entrepreneurs. In particular, this study generates greater awareness among SME entrepreneurs on relational capital and Islamic work ethics as they would espouse initiatives and form successful businesses.